PENGEMBANGAN TEKNOLOGI VIRTUAL REALITY DALAM PEMBELAJARAN KIMIA - Fransiska, Ananda Awaliya; Fitriyani, Aida (Journal of Chemistry Education and Integration, 2024)
AbstractThis research aims to develop and enable Virtual Reality (VR) applications in chemistry learning. The method used is a literature review study, where we review and synthesize relevant previous research. This approach involves gathering, assembling, and analyzing literature from a variety of academic sources to understand the use and effectiveness of VR in chemistry education. The analysis results show that VR has great potential in improving understanding of chemical concepts through three-dimensional visualization and interactive simulations. Previous research shows that VR can increase student engagement and motivation, but it also faces technical and pedagogical challenges. This literature synthesis reveals best practices and pitfalls in research, providing direction for further development. By understanding trends and findings from previous research, this research contributes to the development of more effective and strategic VR applications in chemistry learning, as well as offers recommendations for implementation on a broader scale.Keywords: Virtual Reality, Chemistry Learning Media, Technology